Distributed Intelligent Assistance Robotic System with Sensor Networks Based on Robot Technology Middleware - Songmin Jia; Zhengyin Dong; Xiuzhi Li; Xiongwei Pang; Bing Guo; Shuang Wang; Ke Wang (International Journal of Distributed Sensor Networks)
This paper proposes a distributed intelligent assistant robotic system in order to improve the quality of the elderly people's life in the population aging society. The system is composed of embedded distributed sensor networks and multirobot intelligent platform. In the proposed system, we use SP 2 ATM (simultaneous path planning and topological mapping) with RBPF (Rao-Blackwellized particle filter) for path planning and localization of mobile robots. In order to perform service tasks, an accurate and reliable 3D environment map is reconstructed by using an effective 3D reconstruction technique from multiview stereo. Besides, the system provides user human tracking services based on multifeature mean shift under the double-layer locating mechanism. To improve the feasibility and reliability of the system, this proposed system is developed based on distributed control technology RTM (robot technology middleware). This paper presents the architecture of the proposed system and the experimental results verify effectiveness of the approaches.